Associations between psychiatric morbidity and COVID-19 vaccine hesitancy: An analysis of electronic health records and patient survey. (January 2022) - Eyllon, Mara; Dang, Alexander P.; Barnes, J. Ben; Buresh, John; Peloquin, Gabrielle D.; Hogan, Annika C.; Shimotsu, Scott T.; Sama, Susan R.; Nordberg, Samuel S.
Highlights: Individuals with psychiatric conditions and substance use disorders have elevated risk for severe COVID-19 morbidity and mortality compared to those without. Vaccine hesitancy is more prevalent across those with a wide range of psychiatric conditions. Substance use disorders and tobacco use are independently associated with vaccine hesitancy, controlling for sociodemographic factors. Interventions embedded in mental health services may improve vaccine uptake among individuals with psychiatric conditions and substance use disorders. Abstract: Psychiatric illness confers significant risk for severe COVID-19 morbidity and mortality; identifying psychiatric risk factors for vaccine hesitancy is critical to mitigating risk in this population. This study examined the prevalence of vaccine hesitancy among those with psychiatric illness and the associations between psychiatric morbidity and vaccine hesitancy. Data came from electronic health records and a patient survey obtained from 14, 365 patients at a group medical practice between February and May 2021. Logistic regression was used to calculate odds for vaccine hesitancy adjusted for sociodemographic characteristics and physical comorbidity. Of 14, 365 participants 1, 761 (12.3%) participants reported vaccine hesitancy. Vaccine hesitancy was significantly more prevalent among participants with substance use (29.6%), attention deficit and hyperactivity (23.3%), posttraumatic stress (23.1%), bipolar (18.0%), generalized anxiety (16.5%), major depressive (16.1%), and other anxiety (15.5%) disorders, tobacco use (18.6%), and those previously infected with COVID-19 (19.8%) compared to participants without . After adjusting for sociodemographic characteristics and physical comorbidities, substance use disorders and tobacco use were significantly associated with increased odds for vaccine hesitancy and bipolar disorder was significantly inversely associated with vaccine hesitancy. Interventions to improve uptake in these populations may be warranted.